Knowledge-Driven Automated Service Composition as a Method for Developing Decision Support Systems - Kiyohito Fujishima (Bright Institute, 2022)
A decision support system often necessitates a large amount of effort from both a domain modeling and technological standpoint. Using automated service composition, the study provides a method for minimizing the complexity of decision support system development. The justification for the approach is that many software systems (including decision support systems) today are based on service-oriented architecture, and the development of such systems may be described to some extent as a building composition of services that meet the required requirements. Automated planning algorithms can successfully address the difficulty of creating such compositions. The functional framework of decision support systems, requirements analysis for configurable service-oriented decision support systems and its primary components, and a conceptual model of a configurable service-oriented decision support system are all presented in the article.